2010
DOI: 10.3928/15428877-20100215-54
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Progression of a Long-Standing Lamellar Macular Hole into a Full-Thickness Macular Hole

Abstract: One patient with past ocular history of full thickness macular hole surgically closed in the right eye was followed with diagnostic of lamellar macular hole in the left eye since 2000. After uncomplicated cataract surgery in the left eye in March 2008, the lamellar hole spontaneously progressed to full thickness macular hole. The patient underwent pars plana vitrectomy, membrane peel and gas bubble injection, with successful closure of the macular hole and improvement in the visual acuity. Optical coherence to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Sixteen studies 2,3,5,6 18 with a combined sample of 76 eyes (n = 76) were included (Table 1). Thirteen studies 2,3,6 12,14 17 (n = 40) used ILM peeling, 1 study 5 (n = 32) used inverted ILM flap techniques, and 2 studies 13,18 (n = 4) did not specify the surgical technique.…”
Section: Resultsmentioning
confidence: 99%
“…Sixteen studies 2,3,5,6 18 with a combined sample of 76 eyes (n = 76) were included (Table 1). Thirteen studies 2,3,6 12,14 17 (n = 40) used ILM peeling, 1 study 5 (n = 32) used inverted ILM flap techniques, and 2 studies 13,18 (n = 4) did not specify the surgical technique.…”
Section: Resultsmentioning
confidence: 99%
“…17 Therefore, this possible morphology of MH formation is still reported occasionally. [18][19][20] We postulated that, in this case, the Müller cell cone might have been damaged by a defect of the inner foveal retina and the subsequent development of the ERM seemed to lead to centrifugal disruption of the remaining outer retinal layer at the fovea.…”
Section: Discussionmentioning
confidence: 95%
“…Casparis and Bovey8 noted that the foveal photoreceptor layer did not appear to be thinned or particularly irregular on OCT in more recent LMH, but in patients with long-term LMH, these tissues looked thin and irregular. In addition, there are case reports of patients who progressed from LMH to full-thickness macular hole 3,9. In contrast with these reports, Theodossiadis et al observed spontaneous closure of LMH in two patients 11 and 21 months after the baseline examination 10.…”
Section: Discussionmentioning
confidence: 98%
“…In recent years, there has been increasing evidence that surgery may be beneficial in certain patients with LMH, and surgery is being seen increasingly as a reasonable option compared with observation in more symptomatic patients 8,9. To the best of our knowledge, no study has compared the results of a surgical approach versus observation in these patients.…”
Section: Introductionmentioning
confidence: 99%